Pengaruh Pengetahuan Pajak, Penerapan E-Filing, Pemeriksaan Pajak, dan Sosialisasi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi - Vitri Nurhayati; Mortigor Afrizal Purba (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Purpose of this study is to investigate the impact of tax knowledge, implementation of e-filing, tax audits, and tax socialization on individual taxpayer compliance. This research analyzes primary data, namely from questionnaires that have been distributed via google form with scale likert to 100 individual taxpayers located at KPP Pratama South Batam. The sample selection used in this research used techniques random sampling. Testing of research variables was carried out using descriptive analysis methods, validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, t tests, F tests, and coefficient of determination tests using the SPSS V25 application. The research results show that tax knowledge does not have an effect on individual taxpayer compliance. Meanwhile, there is a significant influence on implementation of e-filling, tax audits, and tax socialization regarding individual taxpayer compliance..